2020
DOI: 10.1109/lawp.2020.2990944
|View full text |Cite
|
Sign up to set email alerts
|

A Curved 3-D Printed Microstrip Patch Antenna Layout for Bandwidth Enhancement and Size Reduction

Abstract: Microstrip patch antennas are widely employed in several applications, thanks to their low profile, low cost, and easy manufacturing. However, the demand for new technologies providing compactness and high performance poses a long-lasting challenge for the antenna designer. Traditional methods for bandwidth improvement and size reduction have some drawbacks, tied mostly to poor radiation performance or troublesome implementation. In this letter, a novel, simple, but effective patch antenna layout exploiting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 16 publications
(16 reference statements)
1
36
0
Order By: Relevance
“…[7] In this study, a 2 x 2 array was used to enhance the performance of patch antenna, and the behaviour of a circularly polarised array at an inclusive range of fold angles and impact of physical reconfiguration were evaluated. [8] The proposed antenna increased the impedance bandwidth from 2.9% (of a standard flat microstrip patch) to 9.0% [9]. Outcomes in this paper demonstrated that the proposed system is a good design choice of microstrip antenna for Bluetooth, Wi-Fi, Wi-MAX, Telemedicine, and UWB applications.…”
Section: Introductionmentioning
confidence: 75%
“…[7] In this study, a 2 x 2 array was used to enhance the performance of patch antenna, and the behaviour of a circularly polarised array at an inclusive range of fold angles and impact of physical reconfiguration were evaluated. [8] The proposed antenna increased the impedance bandwidth from 2.9% (of a standard flat microstrip patch) to 9.0% [9]. Outcomes in this paper demonstrated that the proposed system is a good design choice of microstrip antenna for Bluetooth, Wi-Fi, Wi-MAX, Telemedicine, and UWB applications.…”
Section: Introductionmentioning
confidence: 75%
“…From Eqn. (25) and ( 26), for = 1, we obtain (27) The expression for effective gain given by Eqn. (24) then becomes (28) The resonant resistance R can be calculated using (29) Then from Eqs.…”
Section: Wherementioning
confidence: 99%
“…[26] is achieved by loading the antenna with shorting pins and slots. In [27] the bandwidth is enhanced by simply curving the patch antenna in a partial cylindrical shape. In [28] one-dimensional electromagnetic bandgap ground structures and two-stage beam directors are employed in an inverted-L antenna topology to enhance the bandwidth.…”
Section: Design Example Using Metamaterials Inspired T-matching Networkmentioning
confidence: 99%
“…Substrate materials with a low thickness value are widely preferred as they provide improved performance, enhanced bandwidth, and less restricting structures for radiation areas. Various techniques are utilized to manufacture MAs, including wet-etching, inkjet printing, screen printing, and threedimensional (3D) printing [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. 3D printing has a promising potential in antenna manufacturing as it allows faster, more convenient, and less expensive manufacturing than the conventional tech techniques, known as additive manufacturing [10,11].…”
Section: Introductionmentioning
confidence: 99%